2020
DOI: 10.1088/1757-899x/987/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Biocompatible Graphite–Ti Composite after Laser Ablation in Different Atmospheres

Abstract: The field of biocompatible material surfaces is a widely researched topic. Surface energy, surface topography and surface chemistry are important properties of biocompatible surfaces. These properties contribute to better osseointegration and adhesion of cells to implant surfaces. This article investigates the chemical and phase composition of the surface of a new titanium composite produced by powder metallurgy. Surface oxidation of the graphite– titanium metal matrix composite (TiMMC) after laser beam microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to [22,[77][78][79], the higher surface roughness resulted in a lower value of the contact angle, but with surface oxidation and organic contamination over time, the contact angle increased. The phase composition of the Ti-graphite composite after laser treatment was studied by the authors in [35]. Two types of oxides were detected on the surface of samples after laser ablation in the Ar shielding gas, namely, cubic TiO and rhombohedral Ti 2 O 3 , with a content of 50% and 60%, respectively.…”
Section: Wettability Testmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [22,[77][78][79], the higher surface roughness resulted in a lower value of the contact angle, but with surface oxidation and organic contamination over time, the contact angle increased. The phase composition of the Ti-graphite composite after laser treatment was studied by the authors in [35]. Two types of oxides were detected on the surface of samples after laser ablation in the Ar shielding gas, namely, cubic TiO and rhombohedral Ti 2 O 3 , with a content of 50% and 60%, respectively.…”
Section: Wettability Testmentioning
confidence: 99%
“…To ensure better biocompatibility of the titanium implant surface, numerous mechanical (sandblasting, mechanical grinding, polishing), chemical (oxidation, acid etching, anodization), or physical (ion implantation, physical vapor deposition, laser treatment) surface modification methods can be used [25,26]. Among the aforementioned techniques, surface modification by pulsed laser beam, which represents a fast, easily reproducible, and low contamination process, can be utilized for the preparation of surface textures [27][28][29][30][31], isotropic and anisotropic surface structures [32,33], or biocompatible coatings with the appropriate combination of resultant surface integrity and chemical composition [34][35][36][37]. For example, a study [38] revealed that CO 2 laser treatment helped to significantly enhance cell adhesion and proliferation of MC3T3 and NIH/3T3 cell lines on a TiG5 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of laser energy on the machined surface morphology, roughness, and chemistry of the Ti-graphite composite samples, prepared by pioneering a low-temperature powder metallurgy technique, was investigated and evaluated recently [44,45]. The authors illustrated that the amount of thermal energy incorporated in the working material had a remarkable effect on the machined surface and identified the surface profiles that could promote the osseointegration properties.…”
Section: Introductionmentioning
confidence: 99%